2006
DOI: 10.6026/97320630001130
|View full text |Cite
|
Sign up to set email alerts
|

A database of 389 medicinal plants for diabetes

Abstract: Abstract:Medicinal plants used to treat hypoglycemic and hyperglycemic conditions are of considerable interest to ethno-botanical community as they are recognized to contain valuable medicinal properties in different parts of the plant. The active principles of many plant species with desired properties are isolated to cure ailments such as diabetes type-1 and type-2, respectively. Here, we describe DiaMedBase, a database containing information of medicinal plants for diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 9 publications
0
16
0
1
Order By: Relevance
“…In India, indigenous herbal remedies such as Ayurveda and other Indian traditional medicine have since ancient times used plants in treatment of diabetes[10]. Ethnobotanical studies of traditional herbal remedies used for diabetes have identified more than 1,200 species of plants with hypoglycemic activity [3,11].…”
Section: Introductionmentioning
confidence: 99%
“…In India, indigenous herbal remedies such as Ayurveda and other Indian traditional medicine have since ancient times used plants in treatment of diabetes[10]. Ethnobotanical studies of traditional herbal remedies used for diabetes have identified more than 1,200 species of plants with hypoglycemic activity [3,11].…”
Section: Introductionmentioning
confidence: 99%
“…In this review, many disease-specific databases are observed. Databases for storing medicinal plant information used in asthma (Kasirajan et al, 2007), in diabetes (Arulrayan et al, 2007;Babu et al, 2006;Middha et al, 2009;Singh et al, 2009), in cancer (AAMD, 2011;Fang et al, 2005;Vetrivel et al, 2009), in anti-arthritic plants (Siddiqui et al, 2011) are some of the examples.…”
Section: Disease-specific Databasesmentioning
confidence: 99%
“…In India, a number of plants are mentioned in the ancient literature of Ayurveda and Siddha for the treatment of diabetic conditions. Indigenous remedies have been used in India for the treatment of diabetes mellitus since the time of Charaka and Sushruta [6] . Many Indian plants have been investigated for their beneficial use in different types of diabetes [7] .…”
Section: Introductionmentioning
confidence: 99%